Exploring Social Media Storytelling to promote Tourist Destinations: A case study of thematic villages in Malang City - Agustina, Hiqma Nur; Anyassari, Nugrahaningtyas Fatma; Sakinah, Yanik Lailinas; Rahayu, Eka Listianing (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
The purpose of this study was to investigate the narratives of Kampung Warna-warni Jodipan, Kampung Budaya Polowijen, and Kampoeng Heritage Kajoetangan, three Malang City themed villages that have developed into popular tourist destinations. Social media, especially platforms like Instagram, has become a powerful tool in promoting tourism by enabling destinations to reach global audiences, foster community engagement, and create visually driven narratives that attract visitors. This approach aligns with the Sustainable Developments Goals (SDGs) 11, a globally recognized framework that emphasizes creating inclusive, safe, resilient, and sustainable cities and human settlements worldwide. By promoting these villages through effective Instagram storytelling, tourism managers can support SDG 11’s objectives by highlighting unique cultural heritage while also contributing to local economic and social sustainability. This study used a quantitative descriptive content analysis method. The results revealed that the three thematic villages have not yet fully used storytelling techniques in the content created and posted on Instagram, and have not optimally used tourism components, such as attractions, amenities, and accessibility. These findings suggest that the managers of the Kampung Warna-warni Jodipan, Kampung Budaya Polowijen, and Kampoeng Heritage Kajoetangan should consider incorporating storytelling elements and tourism components in creating content to effectively target audiences and highlight the unique qualities of each village.